The Foker Technique (FT) and Kimura Advancement (KA) for the Treatment of Children with Long-Gap Esophageal Atresia (LGEA): Lessons Learned at Two European Centers - Sroka, Mariusz; Wachowiak, Robin; Losin, Marcin; Szlagatys-Sidorkiewicz, Agnieszka; Landowski, Piotr; Czauderna, Piotr; Foker, John; Till, Holger (European Journal of Pediatric Surgery, 2013)
Introduction We present the experiences from two European centers performing the Foker technique (FT) of esophageal lengthening by axial traction and the Kimura advancement (KA) method of lengthening the upper pouch by extrathoracic resiting a spit fistula (SF) in children with long-gap esophageal atresia (LGEA, gap length > 5 cm).Materials and Methods A total of 15 children were treated (8 pure EA, 6 lower tracheoesophageal fistula [TEF], and 1 upper TEF). Gaps ranged from 5 to 14 cm. Nine children already had a SF. Patients were grouped according to the presence of a SF and the subsequent surgical strategy: Group A (no SF, n = 6) received FT on both pouches. Group B (with SF, n = 6) received KA of SF and FT of the lower pouch. Group C (with SF, n = 3) received closure of the SF and subsequent Foker traction (CSFT) on both pouches.Results Group A: Primary repairs for all six children (mean age 3 months, gap length 6.5 cm) after a mean traction time of 3 weeks and a mean of 2.1 thoracotomies (range 2 to 3). Dilations were required in three out of six for anastomotic strictures with one perforation during the second dilation. Group B: All six children (mean age 16.4 months, gap length 9.5 cm) had a primary anastomosis, although for two it was significantly delayed (48 and 143 weeks traction time) because of infections. The number of thoracotomies ranged from 2 to 8 (mean 3.6). Leaks occurred in five out of six anastomoses (responsive to conservative management). Two children developed severe strictures, which required the anastomosis to be redone. In group C (mean age 10.6 months, gap length 6.5 cm), several major complications occurred. The three SF closures leaked (one iatrogenic) causing severe mediastinitis. CSFT was successful in only one case and the other two children had an esophageal replacement (stomach, jejunum). No deaths occurred in the series.Conclusion FT of both pouches (group A) resulted in primary repairs of all six LGEA patients. The combination of KA and FT (group B) resulted in an equivalent rate of primary repairs, but with an increased number of thoracotomies and rate of complications compared with group A. CSFT (group C) resulted in a high failure rate. More data are needed (we propose a multicenter registry) to elucidate the safety and efficacy of each elongation technique and to establish an algorithm with clearer inclusion and exclusion criteria.
Keywords: long gap; esophageal atresia; Foker; Kimura; multicenter